Hubungan Gaya Mengajar Guru Dengan Motivasi Belajar Siswa Di Sekolah Menengah Kejuruan Negeri Model Gorontalo Kecamatan Botupingge - Veronika Male; Ansar Ansar; Arwildayanto Arwildayanto (Journal of Educational Administration and Leadership, 2021)
Veronika Male. 2021. The Relationship between Teacher Teaching Style and Students Learning Motivation in State Vocational High School Model Gorontalo, Botupingge Sub-district. Undergraduate Thesis. Department of Educational Management. Faculty of Education. State University of Gorontalo. The principal supervisor is Prof. Dr. Ansar, M.Si, and the co-supervisor is Dr. Arwildayanto, M.Pd. This study aims to find out: 1) teacher teaching style in State Vocational High School Model Gorontalo, 2) students learning motivation in State Vocational High School Model Gorontalo, 3) the relationship between teacher teaching style and students learning motivation in State Vocational High School Model Gorontalo. The method used in this research is quantitative by correlational technique. The samples are 76 respondents. The data collection technique uses questionnaires. The result show that: 1) teacher teaching style in State Vocational High School Model Gorontalo is at the percentage of 84.44% or very good criteria, 2) students learning motivation in State Vocational High School Model Gorontalo is at the percentage of 80.58% or good criteria, 3) teacher teaching style and students learning motivation have a significant and positive relationship with a correlation coefficient of 0.763. So that, it is suggested: 1) for school, it is expected to improve students learning motivation to produce quality graduates. 2) for the teacher, it is expected to improve the teaching style to create effective and efficient learning processes. 3) for the researchers, it is expected to strengthen the ability to analyze the teacher teaching style and students learning motivation. Keywords: teacher teaching style, students learning motivation